Medición de estrés en los docentes de la Universidad Antonio Nariño Sede Ibagué (2023)
Stress is a phenomenon that has been studied in different areas of life, including the workplace, and university teaching is no exception. According to Selye's stress theory, stressors can generate cognitive, emotional, and physiological responses that can affect an individual's long-term health. University professors are exposed to stressful factors such as the constant updating of technology and knowledge, making important decisions and introducing effective and innovative changes, multiple parallel jobs, traffic and family, which can affect their job performance. In fact, studies have shown that university teaching can be a profession that carries significant levels of stress.